Analisis Dampak Fasilitas Fiskal pada Kawasan Ekonomi Khusus: Studi Kasus Sei Mangkei - Ivan Krishna Harimurti; Ikhsantino Akbar (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Special Economic Zones (SEZs) are one of the government’s strategic policies to promote economic growth, attract investment, and accelerate regional development through various incentives, including fiscal facilities. This study aims to analyze the impact of fiscal incentives and investment activities on economic development in the Sei Mangkei Special Economic Zone (SEZ) in North Sumatra. The research employs a closed input–output analysis model using the 2016 Domestic Transaction Table of North Sumatra Province at producer prices, which covers 52 economic sectors published by Statistics Indonesia (BPS). The analysis focuses on sectors closely related to the main activities in the Sei Mangkei SEZ, including the chemical industry, plantations, food and beverage manufacturing, electricity, business services, warehousing and transportation, and metal and electronics manufacturing industries. Multiplier analysis and economic impact analysis are applied to examine the intersectoral linkages and the broader economic effects of investment. The economic shock used in the model is based on the value of investment commitments in the Sei Mangkei SEZ obtained from the 2021 SEZ Development Report. The results indicate that investment activities in the Sei Mangkei SEZ generate significant multiplier effects, increasing output not only in directly related sectors but also in other sectors within the regional economy. These findings suggest that the development of the Sei Mangkei SEZ has the potential to strengthen regional economic growth and stimulate broader economic linkages in North Sumatra.